2006
DOI: 10.1073/pnas.0510187103
|View full text |Cite
|
Sign up to set email alerts
|

Designed tumor necrosis factor-related apoptosis-inducing ligand variants initiating apoptosis exclusively via the DR5 receptor

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a potential anticancer drug that selectively induces apoptosis in a variety of cancer cells by interacting with death receptors DR4 and DR5. TRAIL can also bind to decoy receptors (DcR1, DcR2, and osteoprotegerin receptor) that cannot induce apoptosis. The occurrence of DR5-responsive tumor cells indicates that a DR5 receptor-specific TRAIL variant will permit tumor-selective therapies. By using the automatic design algorithm FOLD-X, we success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
194
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(198 citation statements)
references
References 34 publications
3
194
1
Order By: Relevance
“…1, 3), suggesting that other factors regulate the sensitivity at the downstream signaling of the receptors. However, it seems that some leukemia cells undergo apoptotic cell death through signaling by either pro-apoptotic DR4 or DR5, but not both, as has been found for various solid tumors [25,26]. The substantial sensitivity of HL-60 (AML) and U937 (monoblastic leukemia) cells to TRAIL-mediated cytotoxicity, but not to AY4, suggests that DR5 is the main receptor that transduces apoptotic signaling in the leukemia cells.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…1, 3), suggesting that other factors regulate the sensitivity at the downstream signaling of the receptors. However, it seems that some leukemia cells undergo apoptotic cell death through signaling by either pro-apoptotic DR4 or DR5, but not both, as has been found for various solid tumors [25,26]. The substantial sensitivity of HL-60 (AML) and U937 (monoblastic leukemia) cells to TRAIL-mediated cytotoxicity, but not to AY4, suggests that DR5 is the main receptor that transduces apoptotic signaling in the leukemia cells.…”
Section: Discussionmentioning
confidence: 90%
“…The receptor-specific agonistic mAb studies demonstrated that, while various solid tumors were more sensitive to DR5-mediated apoptosis than DR4-induced apoptosis [25,26], primary CLL cells underwent apoptotic cell death almost exclusively through DR4, not DR5 [23,24,27]. However, there have been limited studies of how DR4-or DR5-mediated signaling alone or in combination with chemotherapeutic agents can contribute to apoptosis for other leukemia cells, such as ALL, AML, and CML cells.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced activity of targeted TRAIL might be explained by its action as a quasi membrane-bound form, leading to efficient formation of both TRAIL-R1-and TRAIL-R2-signaling complexes, whereas scTRAIL preferentially binds to TRAIL-R1 and TRAIL decoy receptors. 42 Despite similar expression of both receptors in certain cancer cells, TRAIL-R2 appears as the primary transducer of the TRAIL death signal in many cancer cells, 43 which might account for the higher proapoptotic activity of EGFR-targeted scTRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify and characterize the critical residues involved in dimerization of ZFNs, 3D protein models based on the crystal structure of the native FokI endonuclease 22 25 were established. Although the published crystal structures 22,23 do not provide a clear-cut view of the active enzyme bound to DNA, they offer useful information for structure-aided design of point mutations in order to alter the dimerization behavior of ZFNs (Fig.…”
Section: Protein Modeling and In Silico Mutagenesismentioning
confidence: 99%